2023
DOI: 10.3390/pr11072213
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Activated Water: Physicochemical Properties, Generation Techniques, and Applications

Abstract: Plasma-activated water (PAW) is water that has been treated with atmospheric pressure plasma. Due to the presence of reactive oxygen and nitrogen species (RONS), PAW can be used in various applications such as (1) surface disinfection and food decontamination, (2) enhancement in seed germination, and (3) enhancement in surface cooling in the nucleate boiling regime. Briefly, for surface disinfection, the reactive species in PAW can induce oxidative stress on microbes; for enhancement of seed germination, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…Preclinical and clinical studies have reported that the separate application of NTP and PTW promotes anti-inflammatory and microbicidal functions, facilitating tissue repair and contributing to the restoration of periodontal tissue. The extent of this recovery is contingent on the number of applications, as supported by research such as [49][50][51][52]63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have reported that the separate application of NTP and PTW promotes anti-inflammatory and microbicidal functions, facilitating tissue repair and contributing to the restoration of periodontal tissue. The extent of this recovery is contingent on the number of applications, as supported by research such as [49][50][51][52]63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In such water, there are peaks in the region of 150-200 nm, with low light scattering intensity. It was previously shown that with prolonged contact of freshly distilled water with atmospheric gases, the water becomes saturated with oxygen and nitrogen molecules [35]. In this case, nano-sized clusters of gases, so-called bubstons, are formed in water [36].…”
Section: Study Of the Physicochemical Properties Of Aqueous Igg Collo...mentioning
confidence: 99%
“…The disinfection effectiveness of PAW hinges upon the concentration of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in the PAW. ROS generated in PAW, including hydrogen peroxide(H 2 O 2 ), hydroxyl radical(•OH), and ozone (O 3 ), function as potent oxidizing agents, inducing oxidative stress on the microbial cell membranes and, consequently, bacterial damage and death [7].…”
Section: Introductionmentioning
confidence: 99%
“…Peroxynitrite can accumulate inside cells leading to apoptotic or necrotic cell death [8]. The production of various reactive oxygen and nitrogen species (RONS) depends on the operating parameters of plasma generation, such as the power source, treatment time, feed gases, and electrode materials [7,9]. Gao et al reported that increasing the electrical power from 0 to 160 W led to higher concentrations of OH, H 2 O 2 , NO 3 − , and NH 4 in PAW [4].…”
Section: Introductionmentioning
confidence: 99%